AUGUSTE COMTE DAN FILSAFAT HUKUM - Abu Bakar (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
Augustc Conrtc was thc loundcr of'positivisrn philosphy as his capability in.tbrmulating the ccrtainty law sourcecl liom the value of socr:ety developmcnt. lJis philosphical method through observation toward the 1acts, ancl then thc exprcnrentation to make a phenomenon as the process and thc conlparation tc) research the shophisticated things like in biology and sosiology. The law rhcory ol'l.hrcc dcvcloPirtg cra.ol'socicty, arc thcological cra, thal's ih. lu* 11,,*.,. ,il' gods, ncxt thc nrctalhisical cra, tirat the law starlcd to abstract l.o battlc wotlr destinition, and finally the positive era, when the law was understand unclcr facts and reasorr. The positivism law consist of two kinds that the law ol;losivism is similar with thc acts and sosiological positivism or hisrorical philisophy that gavc thc cltancc fbr historical inclividual lbcts in gcner.al thcory. 'l'hc sosiology differed between social statika that the society is an organic urrity uu.] thc sociat diynarnic that see the mankind as social bcing that develop under thc social larv in history.